Study on surface reaction kinetics of SO2 temperature programmed on sulphur tail gas hydrogenation catalyst. Issue 1 (September 2021) - Su, R; Li, R; Yu, C C
Abstract: This study is aimed to investigate the reaction energy of hydrodesulphurization catalyst for SO2 to H2 S and the desorption energy of H2 S. We used polymath software to fit the experiment data. The result of the fitting shows that the reaction energy is about 96 kJ/mol. In addition, a series of experiments with different heating rate was carried out to get the desorption energy of H2 S on the catalyst. The obtained value is about 169.85 kJ/mol.